PELATIHAN DAN IMPLEMENTASI SISTEM MANAJEMEN KEUANGAN BERBASIS MOBILE PADA PENGELOLA DESA WISATA KREBET BANTUL - Melany Mustika Dewi; Sutarni Sutarni; Lilis Dwi Farida; Safira Trisna Iskandari; Okti Setianing Choiriyah (Universitas Mataram, 2026)
This community service activity was motivated by financial management issues in Krebet Tourism Village, where income and expense records were still documented manually, making them vulnerable to errors, inconsistencies, and a lack of transparency. Such conditions hindered the preparation of accurate and detailed financial reports and potentially affected the effectiveness of tourism management. This program aimed to improve the understanding and skills of Pokdarwis members in using a mobile-based financial application designed to be efficient, realtime, and user-friendly. The methods used included a socialization session, technical training (introduction, demonstration, and hands-on simulation), and evaluation through a post-test to measure participant comprehension. The results indicated a significant improvement, with 100% of participants able to explain the application's functions, record financial transactions correctly, and recognize the importance of digitalization. The application also proved helpful in recording income, expenses, and generating more accurate and organized financial reports. Overall, this activity positively impacted the digital capabilities of tourism managers and supported transparent and sustainable financial governance in Krebet Tourism Village. Therefore, the program successfully achieved its goals by implementing the application and delivering effective training.